2004
DOI: 10.1037/0022-0167.51.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Questionnaire: Is It Sensitive to Changes in Counseling Center Clients?

Abstract: Sensitivity to change of the Outcome Questionnaire (OQ; M. J. Lambert et al., 1996) items, subscales, and total score was evaluated for clients receiving personal counseling in university counseling center settings. OQ data collected for 248 university students who did not receive treatment and 5,553 students who received treatment from 527 therapists employed in 40 university counseling centers nationwide were included in the analyses. Comparisons between the treated and untreated groups indicated that the OQ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
96
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 119 publications
(97 citation statements)
references
References 25 publications
0
96
0
1
Order By: Relevance
“…Furthermore, the items that make up the OQ-45 have been shown to be sensitive to changes in multiple patient populations over short periods of time while remaining relatively stable in untreated individuals [21]. Evidence from factor analytic studies suggests it measures an overall psychological distress factor as well as factors consistent with the 3 subscales [22].…”
Section: The Oq-analyst System For Monitoring and Enhancing Patient Tmentioning
confidence: 99%
“…Furthermore, the items that make up the OQ-45 have been shown to be sensitive to changes in multiple patient populations over short periods of time while remaining relatively stable in untreated individuals [21]. Evidence from factor analytic studies suggests it measures an overall psychological distress factor as well as factors consistent with the 3 subscales [22].…”
Section: The Oq-analyst System For Monitoring and Enhancing Patient Tmentioning
confidence: 99%
“…Concurrent validity is moderate to high (r values of 0.50-0.85) when correlated with measures most often used to assess psychotherapy outcome in clinical trials (Lambert et al, 2004a). Most importantly, the OQ-45 has been shown to be sensitive to change in clients over short time periods, while remaining stable in untreated individuals (Vermeersch, Lambert, & Burlingame, 2000;Vermeersch et al, 2004).…”
Section: Outcome Questionnaire-45mentioning
confidence: 99%
“…The OQ-30 is comprised of the 30 OQ-45 items that are the most sensitive to client change (Vermeersch et al, 2000(Vermeersch et al, , 2004. The OQ-30 assesses the same domains as the OQ-45: subjective discomfort/symptoms, problems in interpersonal relationships, and problems in social role performance.…”
Section: Outcome Questionnaire-30mentioning
confidence: 99%
“…Furthermore, the OQ45.2 shows no significant differences based upon gender or ethnicity (Nebeker, Lambert, & Huefner, 1995). An investigation of the specificity and sensitivity to change during treatment found that the OQ45.2 is largely sensitive to change based on both the overall score as well as the three subscale scores (Vermeersch, Lambert, & Burlingame, 2000;Vermeersch et al, 2004).…”
Section: Expectations Questionnairesmentioning
confidence: 99%